Determining Factors and Strategies for Enhancing Student Focus in Unplugged Coding Learning: A Literature Review - Wibowo, Heri; Yamtinah, Sri; Sukoarno, Sukarno (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
The integration of unplugged coding in elementary schools offers a solution to the lack of devices in implementing the coding curriculum, but its effectiveness depends on student focus and engagement. This study aims to analyze the factors influencing student focus and strategies for maintaining concentration during such learning. The method used is a Systematic Literature Review (SLR) of articles from 2020–2025 on Google Scholar using keywords related to unplugged coding, focus, attention, and elementary school. Articles were selected based on inclusion criteria and then analyzed using content analysis and narrative synthesis techniques. The analysis of 7 articles revealed that student focus is influenced by kinesthetic stimulation, structured collaboration, and a game-based context. The use of manipulatives and gamification enhances attention as well as mastery of algorithms and debugging. With a balanced instructional design, unplugged coding effectively maintains student focus in alignment with their neurocognitive development.